2008
DOI: 10.1128/ec.00411-07
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of a Mechanosensitive Channel Mutant, mid - 1 , in a Filamentous Fungus, Neurospora crassa

Abstract: In the yeast Saccharomyces cerevisiae, the MID1 (mating-induced death) gene encodes a stretch-activated channel which is required for successful mating; the mutant phenotype is rescued by elevated extracellular calcium. Homologs of the MID1 gene are found in fungi that are morphologically complex compared to yeast, both Basidiomycetes and Ascomycetes. We explored the phenotype of a mid-1 knockout mutant in the filamentous ascomycete Neurospora crassa. The mutant exhibits lower growth vigor than the wild type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 36 publications
1
52
1
Order By: Relevance
“…The rapid drop in turgor was followed by a recovery to near original values within 60 min ( Fig. 2a) (Lew et al, 2004(Lew et al, , 2008. Turgor loss occurred in concert with a decline in relative hyphal volume per unit length (Fig.…”
Section: Time-course Of Hyperosmotic-induced Hyphal Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid drop in turgor was followed by a recovery to near original values within 60 min ( Fig. 2a) (Lew et al, 2004(Lew et al, , 2008. Turgor loss occurred in concert with a decline in relative hyphal volume per unit length (Fig.…”
Section: Time-course Of Hyperosmotic-induced Hyphal Changesmentioning
confidence: 99%
“…Time-courses of responses to hyperosmotic treatment. The average time to peak depolarization and onset of sustained hyperpolarization are indicated by vertical bars, as are the onset of ion uptake (Lew et al, 2006(Lew et al, , 2008 and glycerol production (Lew & Levina, 2007). Turgor (a) (the turgor data were previously published in Lew et al, 2004;Lew & Levina, 2007) declines rapidly, as does relative hyphal volume per unit length (V/V i , see Fig.…”
Section: Time-course Of Hyperosmotic-induced Hyphal Changesmentioning
confidence: 99%
“…The role of these upstream sensors in filamentous fungi is largely unknown. Recently, a N. crassa mutant lacking a Mid1 orthologue was found to be affected in calcium homeostasis and vegetative growth (Lew et al, 2008). Moreover, deletion of a Cch1 orthologue affected ascospore discharge and mycelial growth in F. graminearum (Hallen and Trail, 2008).…”
Section: The Calcium/calcineurin Signalling Pathwaymentioning
confidence: 99%
“…Since the mutants displayed wild-type-like growth on minimal medium with small amounts of CaCl 2 , we suggested that sector formation is due to calcium starvation and hyphal polarity effects, as described for mid1 or cch1 deletion mutants in other filamentous fungi (26,27,53). However, when the cell wall was stained with calcofluor white, no differences from the wild type in hyphal morphology were observed, indicating that there were no defects in hyphal polarity or septation.…”
Section: Discussionmentioning
confidence: 87%
“…Differences between B. cinerea, on the one hand, and N. crassa, C. purpurea, and G. zeae, on the other hand, were seen upon treatment with the ionophore A23187, which was shown to act as a mobile ion carrier (27,28,53). In the latter three fungi, addition of the calcium ionophore A23187 and subsequent increases in the [Ca 2ϩ ] cyt did not result in elevated growth of the mutants.…”
Section: Discussionmentioning
confidence: 88%